Pengaruh Pembiayaan Murâbahah Terhadap Peningkatan Usaha Mikro Kecil Menengah di Baitul Mal Wat Tamwi (BMT) Sidogiri Cabang Kabupaten Mempawah - Al-Amin (Program Studi Manajemen Universitas Muhadi Setiabudi, 2023)
The economic empowerment of low-income communities is a central issue in sustaining real sector economic growth. The purpose of this study was to determine the effect of murabahah financing on increasing micro, small and medium enterprises. This research method is a descriptive method with a quantitative approach with analysis using SPSS 18, the population in this study is micro, small and medium enterprises with a total of 50 umkm. The data collection technique used is an indirect communication technique with a tool in the form of a questionnaire or questionnaire. The results of this study are that murabahah financing has a significant effect on increasing micro, small and medium enterprises with an effect of 22.4% and the remaining 77.6% is the influence of other variables that are not in this study (Extranius Variable).